Studi Fenomenologi Akuntabilitas Dalam Proses Konversi Bank Nagari Sumatera Barat Menjadi Bank Nagari Syariah Sumatera Barat - Wellya Fitri; Vanica Sherly (Universitas Negeri Padang, 2020)
This research aims to investigate how members of the organization view the role of accounting and accountability in sharia entities before converting from convensional banks to sharia banks. This research is a type of phenomenological research. Data collection techniques are guided free interviews. The interview were conducted with employees of the Bank of Nagari Syariah Unit of West Sumatera and the sharia Unit of Payakumbuh branch. The results of this research proved that (1)The Imperfect implementation of Sharia accounting on Bank Nagari Syariah Unit of West Sumatera related to the concept of time period in terms of zakat reporting and withdrawal, thus making the implementation of the Islamic accounting system has not fulfilled the rules expected, (2) Low quality of human resources residing in the sharia branches related to sharia accounting and accountability, because they didn’t realizing that the sharia system is run from the basic knowledge of sharia and sharia responsibility as a good Muslim, (3) Sharia units cannot fully run a Sharia products as a whole because is constrained by the capitalist rules that must be followed without any other options such as accounting concepts in monetary units, (4) The low level of public awareness that chooses to become a Sharia Bank client to fully carry out pure sharia from its own instinctively